Analisis Kebijakan Moneter Terhadap Risk-Taking Studi Kasus PT Bank Central Asia Tbk Indonesia Tahun 2024 - Riski Wisnu Prakoso; Giantoro Pamungkas (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Monetary policy is a key instrument in controlling inflation and ensuring a country's economic stability. This study aims to analyze the impact of monetary policy on risk-taking behavior at PT Bank Central Asia Tbk during the year 2024. Using a quantitative approach, secondary data were obtained from the bank's financial statements and official publications from Bank Indonesia. The analysis explores the relationship between interest rates, exchange rate fluctuations, and the bank's lending decisions. The findings indicate that the interest rate cuts implemented by Bank Indonesia encouraged an increase in the volume of credit disbursed by PT Bank Central Asia Tbk, creating a more conducive environment for economic growth. However, this increased risk-taking also brings potential systemic risks, especially in times of economic instability. Additionally, the depreciation of the rupiah exchange rate has implications for the bank’s asset quality, as reflected in a rising Non-Performing Loans (NPL) ratio. These findings emphasize the importance of effective risk management in addressing the challenges faced by the bank. Banks must have strong internal control systems to identify and manage risks related to monetary policy and exchange rate fluctuations. Thus, this study provides valuable insights for bank management and other stakeholders in making strategic decisions that can promote sustainable growth and maintain financial stability.